A bridge over troubled water? Flood insurance and the governance of climate change adaptation. Issue 136 (November 2022) - Hampton, Sam; Curtis, James
Highlights: The flood insurance industry is facing an existential threat from climate change. Effective governance of climate change adaptation cannot rely on markets alone. In the UK, new forms of intervention are being developed by the Flood Re initiative. Structural reform of the flood insurance industry is needed. Abstract: Floods are one of the most commonly occurring natural hazard events globally, and present a significant threat to the UK from climate change. Operating since 2016, Flood Re is an industry-government initiative, set up with the goal of reforming the flood insurance market in order to provide universal, affordable cover for UK households. Principally providing reinsurance services to insurers and including mutualisation arrangements, it aims to withdraw from the market in 2039, having paved the way for risk-reflective pricing without subsidy. Drawing on the theoretical work of Francois Ewald, and empirical data from interviews with 12 key stakeholders and documentary analysis, this paper traces a shift in Flood Re's insurantial imaginary, exemplified by the development of several solutions which go beyond its initial remit of providing reinsurance to private insurers. Findings show that this shift has been driven by the growing realisation that climate change is not merely a complicating factor for the ability to achieve a thriving insurance market, but demands a paradigmatic change in the governance of flood risk. We argue that Flood Re has an opportunity to adopt a leadership role in the governance of climate adaptation, but that it must be expanded to include a wider variety of stakeholders covering land-use planning, housing, consumer and community representatives. That a market for flood insurance that delivers on risk reduction and affordability for all can be brought about without structural reform to the industry nor a strong role for the state, is a delusion in light of climate change.